Efeito de uma sessão de exercício aeróbico nos níveis séricos de fator neurotrófico derivado do cérebro (BDNF) e de seu precursor (proBDNF) em indivíduos após Acidente Vascular Cerebral (AVC) na fase crônica - Mariana Lacerda e Silva (2014)
The brain-derived neurotrophic factor (BDNF) is an important element in the neuronal plasticity process and its levels can be modified after aerobic exercise. Studies have investigated the association between serum levels of BDNF and clinical outcome in patients after stroke (stroke), particularly in the acute phase. However, few studies evaluating individuals in the chronic phase and evaluating the effect of aerobic exercise at these levels. Objective: To evaluate the effect of aerobic exercise session (40 minutes walk on the ground at low intensity) in serum BDNF and its precursor (proBDNF) in individuals after stroke in chronic phase. Materials and Methods: Forty-one subjects (21 healthy individuals and 20 individuals after stroke with a mean of 6.2 years of injury) were assessed for cognitive function (Mini-Mental State Examination, MMSE) and affective (Hospital Scale Hamilton Depression, HADS-D), level of physical activity (Human Activity Profile, PAH), muscle strength of the lower limbs (dynamometer Microfet 2MT) and functional capacity from the six-minute walk test (6MWT ) on the first day of evaluation. On the second day, people had to walk on the ground for 40 minutes at low intensity. Peripheral blood was collected immediately before and after the aerobic exercise session, for measurement of serum BDNF proBDNF and through enzyme-linked immunosorbent assay (ELISA). Results: Individuals of both groups were homogeneous with BMI, cognitive function and emotional function. However, the stroke group the individuals had lower physical activity level (Activity Score Maximum, p = 0.007; adjusted score of activity, p <0.001) and covered a shorter distance in the 6MWT (p <0.001). The basal serum proBDNF (p = 0.426) and BDNF (p = 0.778) were not different between groups. There was no change in the levels of proBDNF (control group, p = 0.778; stroke group, p = 0.422) and BDNF (control group, p = 0.778; stroke group, p = 0.717) after aerobic exercise session. Discussion: individuals after stroke have important physical deconditioning, continuing a vicious cycle of inactivity, which explains the lower level of physical activity and distance covered in the 6MWT. The low intensity, without the gradual increase thereof during aerobic exercise can determinants have been no changes to the proBDNF and BDNF levels in both groups. Conclusion: One bout of aerobic exercise (walking on the ground) for forty minutes at low intensity has failed to modify serum proBDNF and BDNF in the sample. Indeed, there is no consensus in the literature as to the type, time and intensity of exercise shown to modify the levels of this neurotrophic factor.